1987
DOI: 10.1271/bbb1961.51.2417
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic reduction of hexavalent chromium by hexavalent chromium tolerant Pseudomonas ambigua G-1.

Abstract: Whenhexavalent chromium(Cr6+) tolerant Pseudomonasambigua G-l was cultivated in nutrient broth containing 150ppm Cr6+, the Cr6+ content of the broth rapidly decreased. The Cr6+ reducing enzyme found in a cell-free extract of P. ambigua G-l required NADH but not NADPH as a hydrogen donor for the reduction of Cr6+. The specific activities of cell-free extracts of several Cr6+ sensitive mutants derived from P. ambigua G-l showed decreases to one fourth to one tenth of that of P. ambigua G-l. Glucose protected the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 0 publications
3
59
1
2
Order By: Relevance
“…In specific cases, hexavalent Cr serves as the terminal electron acceptor in the respiratory process of certain bacteria. This mechanism will indeed detoxify Cr (VI) while providing energy for bacterial cell growth [42].…”
Section: Resultsmentioning
confidence: 99%
“…In specific cases, hexavalent Cr serves as the terminal electron acceptor in the respiratory process of certain bacteria. This mechanism will indeed detoxify Cr (VI) while providing energy for bacterial cell growth [42].…”
Section: Resultsmentioning
confidence: 99%
“…Cr(VI) reduction is shown to be cometabolic (not participating in energy conservation) in certain species of bacteria, but is predominantly dissimilatory/respiratory under anaerobic conditions (Ishibashi et al, 1990). In the latter process, Cr(VI) serves as a terminal electron acceptor in the membrane electron-transport respiratory pathway, a process resulting in energy conservation for growth and cell maintenance (Horitsu et al, 1987). Most micro-organisms are sensitive to Cr(VI), but some microbial species are resistant and can tolerate high levels of chromate.…”
Section: Biological Cr(vi) Reduction and Removalmentioning
confidence: 99%
“…In the latter process, Cr(VI) serves as a terminal electron acceptor in the membrane electron-transport respiratory pathway, a process resulting in energy conservation for growth and cell maintenance (Horitsu et al, 1987;Ishibashi et al, 1990). In the dissimilatory/respiratory process, electrons are donated from the electron donor to Cr(VI) via NADH (Chirwa & Wang, 1997a).…”
Section: Proposed Cr(vi) Reduction Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further evidence suggested that cytochrome c548 was involved in the reduction of Cr (VI) by membrane vesicles. In the presence of H2 and excess of hydrogenase, cytochrome C3, a periplasmic protein, in the soluble cell free fraction of D. vulgaris (Lovley and Coates, 1997), reduced Cr (VI), 50 times faster than did the Cr (VI) reductase of P. ambigua with NADH and NADPH, as electron donor (Horitsu et al, 1987). Under anaerobic condition Cr (VI) reduction is due to the action of enzymes associated with membranes of the electron transfer system (Cervantes and Campos, 2007).…”
Section: Introductionmentioning
confidence: 98%